Biophysical investigation of interactions between sorbic acid and human serum albumin through spectroscopic and computational approaches. (13th April 2021) - Raza, Muslim; Jiang, Yang; Ahmad, Bashir; Rahman, Ata ur; Raza, Saleem; Khan, Ajmal; Tahir, Kamran; Hassan, Said; Khan, Saifullah; Yuan, Qipeng
Abstract : This work provides an effective strategy to analyze the SA-induced microenvironmental changes in the HSA macromolecule, and also highlights the medicinal importance of SA. Abstract : In this study, we investigate the mechanism underlying the binding of SA with HSA by multiple spectroscopic and computational approaches. The topographic changes in the native HSA and HSA–SA structure and behaviours were explored by atomic force microscopy (AFM). Moreover, other advanced spectroscopic methods such as fluorescence, Fourier transform infrared (FT-IR) and circular dichroism (CD) spectroscopy should be used to investigate and understand the binding mechanism of the HSA–SA complex. The interaction of HSA and SA takes place via a static quenching mechanism as observed from fluorescence spectroscopy. After the interaction between SA and HSA, the complex (HSA–SA) molecular dimensions have been increased as confirmed from the AFM results. Different thermodynamic parameters, such as Δ H (−29.366 kJ mol −1 ) and Δ S (+108.149 J mol −1 K −1 ), were calculated to explore the binding nature of HSA–SA, which is mainly contributed by hydrophobic contacts and hydrogen bonds. The site marker displacement and molecular modelling studies suggested that the SA can bind on the site I of HSA. Slight conformational changes of HSA–SA were observed from the CD and IR spectra. Together, this study will provide insights for the food industry on the safety and biological action of SA in the human body.